The Influence of Digital - Based Strategic Management in Increasing Consumer Purchasing Interest - Astitiani, Ni Luh Putu Surya; Putra, I Gede Karang Komala; Widnyani, Ni Made (Journal of Economics and Public Health, 2024)
The study delves into exploring the impact of digital-based strategic management on consumer purchasing interest, particularly focusing on the local wisdom product "Tedung Bali." Situated within the captivating backdrop of the Mengwi Traditional Village in the Badung Regency, the research embarks on a quantitative journey employing univariate and bivariate analysis techniques. The primary data, collected through meticulously crafted questionnaires administered to 123 enterprising individuals involved in the production of "Tedung Bali," forms the cornerstone of this investigation. Utilizing the Chi-Square test as its analytical tool, the study aims to unravel the intricate relationship between the utilization of social media platforms and consumer inclination towards purchasing "Tedung Bali" products. The findings illuminate a compelling correlation, underscoring the pivotal role of social media engagement in shaping consumer behavior towards these indigenous treasures. Furthermore, the demographic profile of respondents reveals intriguing insights, with a predominant representation of males in the 41-50 age bracket, possessing a high school or equivalent educational background. These demographics serve as invaluable markers, offering nuanced perspectives on consumer preferences and behaviors within the targeted market segment. The implications of this research extend beyond the realms of academia, resonating profoundly in the practical domain. By advocating for the integration of digital-based management strategies in the marketing endeavors of local wisdom products, the study underscores a pathway towards achieving tangible success amidst a fiercely competitive market landscape. This strategic alignment promises not only to elevate the visibility and desirability of "Tedung Bali" products but also to foster a sustainable ecosystem conducive to the preservation and promotion of cultural heritage.